Prevalence of depressive symptoms and symptoms of post-traumatic stress disorder among newly arrived refugees and asylum seekers in Germany: systematic review and meta-analysis - Hoell, Andreas; Kourmpeli, Eirini; Salize, Hans Joachim; Heinz, Andreas; Padberg, Frank; Habel, Ute; Kamp-Becker, Inge; Höhne, Edgar; Böge, Kerem; Bajbouj, Malek (BJPsych Open, 2021)
Background - In total numbers, Germany has faced the largest number of refugees and asylum seekers (RAS) in Europe in the past decade. Although a considerable proportion have experienced traumatic and stressful life events, there is no systematic review to date examining the prevalence of depressive symptoms and post-traumatic stress disorder (PTSD) symptoms in RAS in Germany. - - Aims - To calculate the prevalence of depressive symptoms and PTSD symptoms in the general population of RAS living in Germany after the year 2000 and explore the impact of study- and participant-related characteristics on prevalence estimates. - - Method - We systematically searched PubMed, CINAHL, PsycINFO, PSYNDEX, Academic Search Complete, Science Direct and Web of Science from January 2000 to May 2020 to identify articles reporting prevalence of depressive symptoms and PTSD in RAS in Germany (PROSPERO registration number: CRD42020182796). - - Results - In total, 31 different surveys met inclusion criteria with 20 surveys reporting prevalence estimates of depressive symptoms and 25 surveys symptoms of PTSD. Based on screening tools, the pooled prevalence estimate of PTSD symptoms was 29.9% (95% CI 20.8-38.7%) and of depressive symptoms 39.8% (95% CI 29.8-50.1%). Heterogeneity was large within and between subgroups. In multivariate meta-regressions on depressive symptoms, heterogeneity was largely explained by survey period, length of field period and study quality. - - Conclusions - Prevalence rates of depressive symptoms and PTSD symptoms in RAS are notably large. They exceed the prevalence in the general German population. As a result of high heterogeneity, however, pooled prevalence rates should be interpreted with caution.
Gesehen am 12.10.2021